Obesity in pregnancy as a model to identify women at risk for later metabolic syndrome. (2nd January 2018) - Neri, C.; Di Cesare, C.; Labianca, A.; Viggiano, M.; Caruso, A.; Paradisi, G.
Abstract: The aim of our study is to identify – in a cohort of obese women – cardiovascular and clinical risk factors in women with previous complicated pregnancies and protective factors in women with previous physiological pregnancies. A total of 135 nonpregnant obese women referring to Policlinico Gemelli in Rome were prospectively collected in 2009–2010. Thirty-two women matched inclusion criteria: 16 reported a previous physiological pregnancy and 16 reported previous obstetric complications. A clinical, instrumental and laboratory evaluation has been performed for each patient. Statistical analysis was performed using StatView Software. Values are expressed as mean ± standard error (SEM). All tests were two-tailed with a confidence level of 95% ( p < .05). Statistically significant reduced flow-mediated dilatation ( p = .0338), increased serum values of vascular cell adhesion molecule ( p = .0154) and higher systolic blood pressure values ( p = .0427) have been detected in obese women with previous complicated pregnancies due to gestational diabetes and/or hypertension. In conclusion, obese patients with previous complicated pregnancies develop signs of endothelial dysfunction in the postpartum period. Future research should focus on the early identification of possible molecular mechanisms implicated in the development of glyco-metabolic and cardiovascular diseases in obese patients, since they are at higher risk of metabolic syndrome.